School Engagement among Youth in Canadian Forces Families: A Comparative Analysis - Robson, Karen; Albanese, Patrizia; Harrison, Deborah; Sanders, Chris (Alberta Journal of Educational Research, 2014)
There has been a growing body of literature on adolescents in military families since 2002. This research has focused on how frequent moves and parental deployments are two unique potential stressors for youth in military families, and are associated with negative school outcomes. Analyzing data collected from a school in a military community, and data from a national sample of Canadian youth, we examine the impact of military stressors on the school engagement of youth in military families. While we found evidence of residential mobility contributing to negative school engagement outcomes, we also found a positive association between school engagement and parental deployments. Surprisingly, relative to both the civilian youth in our sample and the national sample, military youth exhibited higher levels of school engagement when a parent has been deployed. Depuis 2002, de plus en plus d’études ont été publiées sur les adolescents de familles de militaires. Cette recherche explique que les déplacements fréquents et les déploiements d’un parent constituent pour ces jeunes des agents de stress potentiels et uniques, et qu’ils sont associés à des résultats scolaires négatifs. Nous avons analysé des données provenant d’une école dans une communauté militaire ainsi que des données tirées d’un échantillon national de jeunes canadiens pour étudier l’impact des agents de stress d’origine militaire sur l’implication scolaire chez les jeunes de familles de militaires. Si nous avons trouvé des indications que la mobilité résidentielle contribuait aux résultats scolaires négatifs, nous avons également trouvé une association positive entre l’implication scolaire et les déploiements d’un parent. Étonnamment, nous avons constaté que, comparés aux jeunes civils dans notre échantillon et dans l’échantillon national, les jeunes de familles de militaires manifestent plus d’implication scolaire pendant les déploiements d’un parent.